Implementation of Fuzzy Search and Audio Player for Web-Based Quranic Verse Retrieval - Dewi Primasari; Firman Hakim; Muhammad Danise Raditya Saneistha; Ihsan Wahid Cahya (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
This study aims to develop a web-based Quranic search system integrating fuzzy search and audio player features to address typographical errors in user inputs and enhance accessibility. Employing the Prototype Development Model, we implemented the Levenshtein Distance algorithm via Fuse.js for tolerance-based text matching and integrated an interactive audio player for verse recitation. Testing with typo variations revealed optimal performance at an 80–85% similarity threshold, achieving 92% user satisfaction in handling common misspellings (e.g.,